Inflammasome Priming Mediated via Toll-Like Receptors 2 and 4, Induces Th1-Like Regulatory T Cells in De Novo Autoimmune Hepatitis - Arterbery, Adam S.; Yao, Jie; Ling, Andrew; Avitzur, Yaron; Martinez, Mercedes; Lobritto, Steven; Deng, Yanhong; Geliang, Gan; Mehta, Sameet; Wang, Guilin; Knight, James; Ekong, Udeme D. (Frontiers in Immunology, 2018)
De novo autoimmune hepatitis (DAIH) is an important cause of late allograft dysfunction after liver transplantation, but its cause and underlying pathogenesis remains unclear. We sought to identify specific innate and adaptive immune mechanisms driving the pro-inflammatory cytokine secreting regulatory T cell phenotype in DAIH and determine if modulation of these pathways could resolve the inflammatory milieu observed in the livers of patients with DAIH. Here we demonstrate Toll-like receptors 2 & 4 mediated Inflammasome activation in CD14++ monocytes, a finding that is key to maintaining dysfunctional regulatory T cells in patients with DAIH. Furthermore, silencing of TLR 2 & 4 in CD14++ monocytes prevented activation of the inflammasome and significantly decreased IFN-γ production by FOXP3+ regulatory T cells. We also observed significantly increase in expression of TNFAIP3 (Tumor Necrosis Factor α-induced protein 3), a negative regulator of the NLRP3 Inflammasome, in monocytes/macrophages of liver transplant subjects who have normal allograft function and do not have DAIH. TNFAIP3 expression was virtually absent in monocytes/macrophages of patients with DAIH. Our findings suggest that autoimmunity in DAIH is promoted by CD14++ monocytes predominantly through activation of inflammatory signaling pathways.